Communications to the Editor—A Correction for “Optimal Policy for a Multiproduct Dynamic, Nonstationary Inventory Problem” - anonymous (Management Science, 1970)
I am indebted to Lowell Bruce Anderson of Nothwestern University for pointing out to me that Theorems 6.1 and 6.2 in my paper “Optimal Policy for a Multiproduct Dynamic, Nonstationary Inventory Problem,” (Management Science, Vol. 12, No. 3 (November 1965), pp. 206–222) are false as stated. The theorems become true if we replace the weak hypothesis (6.1) with the stronger hypothesis (6.3).